Identification of mechanical parameters of urea-formaldehyde microcapsules using finite-element method. (1st February 2019) - Wang, X.F.; Han, R.; Tao, J.; Han, T.L.; Zhu, G.M.; Tang, J.N.; Han, N.X.; Xing, F.
Abstract: To obtain the mechanical parameters for a microcapsule, such as the Young's modulus, yield stress, and hardening coefficients using different mechanical constitutive models, parameter identification must be implemented using inverse analysis. In the present study, a new approach combining the finite-element method and an optimisation procedure is proposed for determining the constitutive parameters of urea-formaldehyde microcapsules, in which three types of elastic-plastic constitutive models are considered: the power-law hardening model, the elastic-perfectly plastic model, and the elastic-perfectly plastic model with linear hardening. A nonlinear optimisation procedure is applied to determine the minimum of the multivariable objective function, which is defined as the norm of the difference between the numerical and experimental results. The efficiency and robustness of the proposed method are verified with different initial values and numbers of elements. The force-displacement curves from a numerical simulation show good agreement with the experimental data, indicating that the proposed approach and the mechanical parameters determined are reliable.